Recent Progress on Polymers of Intrinsic Microporosity and Thermally Modified Analogue Materials for Membrane‐Based Fluid Separations. Issue 9 (28th July 2021) - Wang, Yingge; Ghanem, Bader S.; Ali, Zain; Hazazi, Khalid; Han, Yu; Pinnau, Ingo
Abstract : Solution‐processable amorphous glassy polymers of intrinsic microporosity (PIMs) are promising microporous organic materials for membrane‐based gas and liquid separations due to their high surface area and internal free volume, thermal and chemical stability, and excellent separation performance. This review provides an overview of the most recent developments in the design and transport properties of novel ladder PIM materials, polyimides of intrinsic microporosity (PIM–PIs), functionalized PIMs and PIM–PIs, PIM‐derived thermally rearranged (TR), and carbon molecular sieve (CMS) membrane materials as well as PIM‐based thin film composite membranes for a wide range of energy‐intensive gas and liquid separations. In less than two decades, PIMs have significantly lifted the performance upper bounds in H2 /N2, H2 /CH4, O2 /N2, CO2 /N2, and CO2 /CH4 separations. However, PIMs are still limited by their insufficient gas‐pair selectivity to be considered as promising materials for challenging industrial separations such as olefin/paraffin separations. An optimum pore size distribution is required to further improve the selectivity of a PIM for a given application. Specific attention is given to the potential use of PIM‐based CMS membranes for energy‐intensive CO2 /CH4, N2 /CH4, C2 H4 /C2 H6, and C3 H6 /C3 H8 separations, and thin film composite membranes containing PIM motifs for liquid separations. Abstract : This review provides an overview of recent research progress on polymers of intrinsic microporosity (PIMs) for membrane‐based fluid separations, including pristine PIMs and PIM‐derived thermally‐rearranged and carbon molecular sieve membranes. Challenges and opportunities are identified for these materials in energy‐intensive separations such as CO2 /CH4, C2 H4 /C2 H6 and C3 H6 /C3 H8 separations, as well as for thin‐film composite membranes containing PIM motifs in liquid applications.